Unraveling the nature of electric field- and stress- induced structural transformations in soft PZT by a new powder poling technique. (28th January 2015) - Kalyani, Ajay Kumar; V, Lalitha K; James, Ajit R; Fitch, Andy; Ranjan, Rajeev
Abstract: A 'powder-poling' technique was developed to study electric field induced structural transformations in ferroelectrics exhibiting a morphotropic phase boundary (MPB). The technique was employed on soft PZT exhibiting a large longitudinal piezoelectric response ( d 33  ∼ 650 pC N −1 ). It was found that electric poling brings about a considerable degree of irreversible tetragonal to monoclinic transformation. The same transformation was achieved after subjecting the specimen to mechanical stress, which suggests an equivalence of stress and electric field with regard to the structural mechanism in MPB compositions. The electric field induced structural transformation was also found to be accompanied by a decrease in the spatial coherence of polarization.